Leadership as a female political characteristic in Serbia - Vuković Ana (Srpska Politička Misao)
The common notion in our literature about female political leadership insists on patriarchal prejudices as the root cause of the underrepresentation of women in political institutions. This paper points out the dialectical interweaving of this cause with another often underestimated cause: worse political leadership characteristics among certain members of the (female) political (sub)elite. The issue is the dialectical connection of these two causes, with the effect of a feedback loop of negative synergy: the weaker presence of women in political institutions leads to fewer opportunities for gaining political experience and a more limited pool for staff recruitment, which is why some female politicians have weaker characteristics needed for political leadership; on the other hand, this handicap of theirs strengthens patriarchal prejudices against women and further strengthens the reduced presence of women in political institutions. This paper aims not to criticize the political electoral system but to point out the controversies of female leadership as a 'specific' political pattern.